Virtual Network Function Migration Method Based on Topology and Resource Awareness - YANG Yong, MENG Xiangru, KANG Qiaoyan, HAN Xiaoyang (Jisuanji kexue yu tansuo, 2021)
In the network function virtualization environment, aiming at the load imbalance of network, a topology and resource-aware virtual network function migration method (TRA-VNFM) is proposed. Firstly, according to the computing, storage and forwarding resource occupancy of the underlying network, the two-level dynamic threshold is set to classify the overload degree of physical nodes, and at the same time, the corresponding migration judgment conditions are formulated and the set of destination nodes to be migrated is calculated. Among them, high-overload nodes have priority to implement migration and have lower migration success conditions. Secondly, for the virtual network function deployed on the overload node, the resource-aware algorithm is used to set its migration weight.The more overload resources the virtual network function occupies, the larger its migration weight, combining the migration weight and resource demand to select the virtual network function to be migrated. Finally, the topology-aware algorithm of extreme value interaction is used to evaluate the nodes in the migration destination node set, taking the node with the highest evaluation as the migration destination node by considering all kinds of resource occupancy, processing delay and topological properties. Simulation experiments show that compared with the previous virtual network function migration methods, this method not only reduces the migration time, but also has better performance in the average delay of the service function chain, the revenue to expense ratio of network and the degree of load balancing.